2020
DOI: 10.3390/plants9091202
|View full text |Cite
|
Sign up to set email alerts
|

Recent Strategies for Detection and Improvement of Brown Planthopper Resistance Genes in Rice: A Review

Abstract: Brown planthopper (BPH; Nilaparvata lugens Stal) is considered the main rice insect pest in Asia. Several BPH-resistant varieties of rice have been bred previously and released for large-scale production in various rice-growing regions. However, the frequent surfacing of new BPH biotypes necessitates the evolution of new rice varieties that have a wide genetic base to overcome BPH attacks. Nowadays, with the introduction of molecular approaches in varietal development, it is possible to combine multiple genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 116 publications
(160 reference statements)
0
24
0
Order By: Relevance
“…Studies were initiated during 1960s to identify, characterize and utilize rice land races with resistance to BPH and WBPH (Pathak et al 1969 ; IRRI 1979 ; Heinrichs et al 1985 ). So far about 40 major genes and 72 QTLs conferring resistance to BPH and 19 major genes and 75 QTLs conferring resistance to WBPH have been reported from cultivated rice and its wild relatives (Fujita et al 2013 , Ling and Weilin 2016 ; Du et al 2020 ; Haliru et al 2020 ). Using some of these genes or combinations thereof, several rice varieties possessing BPH resistance have been developed and released for cultivation since 1980s (Khush and Brar 1991 ; Brar et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies were initiated during 1960s to identify, characterize and utilize rice land races with resistance to BPH and WBPH (Pathak et al 1969 ; IRRI 1979 ; Heinrichs et al 1985 ). So far about 40 major genes and 72 QTLs conferring resistance to BPH and 19 major genes and 75 QTLs conferring resistance to WBPH have been reported from cultivated rice and its wild relatives (Fujita et al 2013 , Ling and Weilin 2016 ; Du et al 2020 ; Haliru et al 2020 ). Using some of these genes or combinations thereof, several rice varieties possessing BPH resistance have been developed and released for cultivation since 1980s (Khush and Brar 1991 ; Brar et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Using some of these genes or combinations thereof, several rice varieties possessing BPH resistance have been developed and released for cultivation since 1980s (Khush and Brar 1991 ; Brar et al 2009 ). With advent of molecular marker technology almost all the BPH R genes have been mapped with linked markers (Du et al 2020 , Haliru et al 2020 ). It has been observed that 30 R genes are located in six clusters on four chromosomes i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, there has been a growing interest in using molecular tools during the breeding of rice varieties with anti-herbivore resistance [ 11 , 12 , 13 ]. By applying marker-assisted selection, researchers have successfully tagged and transferred one or more resistance genes from donor rice varieties to a range of high-yielding varieties (reviewed by Horgan et al 2018 [ 14 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large number of major anti-planthopper or anti-leafhopper genes that have been identified in rice (currently about 60 genes [ 11 , 12 , 16 ]), the resistance mechanisms associated with these genes are often poorly understood. However, the functioning of some of the major resistance genes was elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation